Relationship Between Exercise and Alzheimer’s Disease: A Narrative Literature Review - Meng, Qing; Lin, Muh-Shi; Tzeng, I-Shiang (Frontiers in Neuroscience, 2020)
This narrative review aimed to summarize evidence regarding the responses to exercise among patients with preclinical Alzheimer’s disease (AD) and the effectiveness of long-term exercise interventions in improving cognitive function and neuropsychiatric symptoms. We performed a narrative review of existing literature on the effectiveness of long-term exercise interventions in improving cognitive function and neuropsychiatric symptoms in patients with AD. Patients with AD who presented with long-term exercise interventions appeared to have improved blood flow, increased hippocampal volume, and improved neurogenesis. Most prospective studies have proven that physical inactivity is one of the most common preventable risk factors for developing AD and that higher physical activity levels are associated with a reduced risk of AD development. Physical exercise seems to be effective in improving several neuropsychiatric symptoms of AD, notably cognitive function. Compared with medications, exercise has been shown to have fewer side effects and better adherence.